Cost Control Strategies in The Covid-19 Pandemic Using The Balanced Scorecard in The Yogyakarta PDHI Islamic Hospital - Cahyo Prihatmoko; Kusbaryanto Kusbaryanto; Nur Hidayah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hospitals are the front line in tackling the covid outbreak but personal protective equipment (PPE) is becoming increasingly scarce. This makes Health service management increasingly ineffective and inefficient. The hope is that hospitals will be able to navigate this phase of the epidemic by turning all obstacles into hope and all opportunities into strengths. Thus, regardless of the current crisis and conditions, the hospital can survive and try to continue to develop.Purpose: The purpose of this research is to develop a strategy for controlling costs in order to maintain and even grow hospital performance during the Covid-19 pandemic.Methods: This research is a qualitative research with a case study approach conducted at RSIY PDHI. The research design uses an approach to explore and understand organizations by presenting a comprehensive overview and reporting detailed descriptions of information sources and preparing them without intervention from the researcher.Research Results and Findings - The overall strategic goals of the organization are categorized into 4 (four) perspectives, namely financial goals, customer goals, internal business process goals, and growth and learning goals. From a financial perspective, three strategic targets are set, namely revenue growth, cost reduction and profitability improvement. From the customer's perspective, four strategic targets are set, namely, increasing the quality and quality of service, increasing customer satisfaction, increasing the quality of customer relationships, and improving the image of the hospital. From the perspective of internal business processes, three strategic targets are set, namely the integration of internal service processes, the improvement of the quality of the service process to customers, and the increasing speed of the service innovation process. From the growth and learning perspective, three strategic targets are set, namely increasing employee capabilities, increasing employee satisfaction, and increasing the use of integrated information systems. From all these targets, key indicators of each strategic target have been set, namely indicators of growth and learning with a target of 95% employee retention and 40 hours of employee training per year. The next indicator is the internal business process with a target response time of < 5 minutes and a target service waiting time of < 10 minutes. Then the customer indicator with a target of 1,000 new customers per year and an old customer retention target of 80%. Finally, financial indicators with a target of 10% revenue growth, 5% cost efficiency and 15% profitability.Originality-This research was conducted in a hospital, because in the era of universal health coverage, the role of the hospital was very strategic. This research focuses on a comprehensive planning analysis from both financial and non-financial aspects.